A Study on Selected Texts of the Islamic Poetry in Northern Nigeria in the 17th and 18th Centuries | دراسة تحليلية لنصوص مختارة من الشعر الإسلامي بشمال نيجيريا خلال القرنين السابع عشر والثامن عشر الميلادين - Abdulsalam Muhammad Usman; Lateef Onireti Ibraheem (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2020)
Nigerian Scholars, like their counterpart in West Africa, studied Arabic in other to understand Islam. This research studied selected text from Islamic poetry composed in Arabic by the Borno Kingdom and Hausaland poets in the eighteen and seventeen centuries in Northern Nigeria. The aim is to panoramically bring to fore the social, political, economic, educational and religious features embedded in the poetry as well as ascertain its quality. Hence the paper discusses, after introduction, Nigeria and the advent of Islam vis a vis Arabic Language, highlights selected poems, studied and criticized its contents based on the theory of Al-Adabul Islami (Islamic Literature). Descriptive method was adopted to analyse the selected poems. At the end of the study, it was discovered that the poetry of this era conformed to the theory of Al-Adabul Islami in its forms and contents, because the poets who composed it adhered strictly to Islamic teachings in their ideas, selection of themes and modes of expression. The language used is also of high standard and derived it strength from the Quran, Sunnah and other Islamic sources.